Experiences of Recovery in EPAPSY’s Community Residential Facilities and the Five CHIME Concepts: A Qualitative Inquiry - Apostolopoulou, Antigoni; Stylianidis, Stelios; Issari, Philia; Chondros, Panagiotis; Alexiadou, Amalia; Belekou, Pepy; Giannou, Charalambos; Karali, Eleni K.; Foi, Vana; Tzaferou, Fotini (Frontiers in Psychiatry, 2020)
In the context of the reform of psychiatric services in Greece, the debate about the concept of recovery is still growing. Recovery is defined as the process through which people with mental health challenges rebuild and further develop significant personal, environmental, social and intellectual relationships and try to cope with the detrimental effects of discrimination through empowerment. The present qualitative study aims to explore the experiences of people living in EPAPSY’s community residential facilities focusing mainly upon the key concepts of the CHIME (connectivity, hope, identity, meaning, and empowerment) conceptual framework of recovery. To this end, semi-structured interviews were conducted with seven participants living and receiving mental health care in a residential facility of EPAPSY. The participants’ accounts were analysed using thematic analysis in a deductive and inductive manner. The research findings highlighted, among others, the challenges the participants faced during their early years in family and school, the experience of the revolving door effect, and the perceived turn their life took when they were transferred to a community residential facility, thus opening a new chapter in their lives. Of the five CHIME concepts, all are present in the participants’ accounts, with emphasis given to a meaningful present, a need to feel “normal” again, and a positive outlook for the future, both for themselves and their relationships, despite the persistence of certain difficulties.